2023
DOI: 10.3390/app13137601
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization of a Two-Stage Helical Gearbox Using Taguchi Method and Grey Relational Analysis

Abstract: This paper presents a novel approach to solve the multi-objective optimization problem designing a two-stage helical gearbox by applying the Taguchi method and the grey relation analysis (GRA). The objective of the study is to identify the optimal main design factors that maximize the gearbox efficiency and minimize the gearbox mass. To achieve that, five main design factors. including the coefficients of wheel face width (CWFW) of the first and the second stages, the allowable contact stresses (ACS) of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…where X is the vector that represents the design variables. A two-stage helical gearbox has five main design parameters: u 1 , X ba1 , X ba2 , AS 1 , and AS 2 [10]. Moreover, it has been demonstrated that the maximum values of AS 1 and AS 2 match their ideal values [10].…”
Section: Constrainsmentioning
confidence: 99%
See 2 more Smart Citations
“…where X is the vector that represents the design variables. A two-stage helical gearbox has five main design parameters: u 1 , X ba1 , X ba2 , AS 1 , and AS 2 [10]. Moreover, it has been demonstrated that the maximum values of AS 1 and AS 2 match their ideal values [10].…”
Section: Constrainsmentioning
confidence: 99%
“…A two-stage helical gearbox has five main design parameters: u 1 , X ba1 , X ba2 , AS 1 , and AS 2 [10]. Moreover, it has been demonstrated that the maximum values of AS 1 and AS 2 match their ideal values [10]. Consequently, u 1 , X ba1 , and X ba2 -the three main design factors-have been selected as variables for the optimization issue in this work.…”
Section: Constrainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings proposed speed having major impact on wear consequence rather than load and reinforcement addition. Le and Vu [ 20 ] utilized a multi-objective optimization technique to maximize gearbox efficiency and minimize its mass of a two-stage helical gear box by identifying different design factors. Taguchi method and grey relation analysis is used to identify that gear box ratio of first stage has a major influence on minimizing gearbox ratio and maximising the efficiency of gearbox.…”
Section: Introductionmentioning
confidence: 99%
“…Le and N.P. Vu [15] to investigate the MOOP of building a two-stage helical gearbox. The aim of this study was to determine the ideal fundamental design parameters that enhance gearbox efficiency while decreasing gearbox mass.…”
Section: Introductionmentioning
confidence: 99%